Location Design of GIS-Based Temporary Evacuation Sites (TES) by Considering the COVID-19 Pandemic Situation: A Case Study in Padang City) - Liperda, Rahmad Inca; Sukarno, Iwan; Yenda, Natasha Utami Syave (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Padang City is an area that is predicted to occur in the Mentawai Megathrust disaster. In dealing with these potential disasters, proper planning is needed to reduce the impact of disasters. The exact location of the Temporary Evacuation Sites (TES) will affect the safety level of the community. However, based on the current situation, the COVID-19 pandemic adds to the complexity of disaster management. Therefore, anticipatory steps are needed to prevent the spread of disease in the environment. This study aims to design a TES location-allocation to deal with the potential Mentawai Megathrust disaster in Padang City by adjust to physical distancing health protocols. Determination of the location-allocation in this study is using Network Analysis extension namely Maximum Capacitated Location Problem (MCLP) in Geographic Information Systems (GIS). In addition, this study uses an evacuation time scenario with an interval of 3-30 minutes consisting of two different scenarios involving the use of community response times to disasters. The location-allocation results consist of four results based on the scenario of evacuation time and the addition of Proposed TES. Based on the location-allocation results, with the addition of Proposed TES, the maximum number of people that can be accommodated is only around 34-39 percent in both evacuation scenarios. This shows that there is a need for further design related to both Existing TES and Proposed TES so that the percentage of the number of people who can be accommodated can increase.